α-Amylase Inhibitor Peptides Derived from Goat Casein Tryptic Hydrolysate - Aulyawati, Nurwardian; Anwar, Chairil; Raharjo, Tri Joko (Universitas Gadjah Mada, 2026)
This study explores the potential of bioactive peptides derived from hydrolyzed goat milk casein as α-amylase inhibitors, with implications for diabetes management. Goat milk casein was hydrolyzed using trypsin at varying enzyme-to-protein ratios to achieve different degrees of hydrolysis (DH). The optimal enzyme-to-protein ratio of 1:40 yielded the highest DH (31.31%). The resulting hydrolyzates were fractionated using strong cationic exchange solid-phase extraction (SCX-SPE), and their α-amylase inhibitory activity was evaluated. The fraction collected at pH 5 exhibited the highest α-amylase inhibition, with an inhibition value of 76.88% and an IC50 of 221.69 μg/mL. This fraction also contained the highest total peptide mass (1,208.9 μg). The enzyme kinetic study demonstrates an uncompetitive inhibition by fraction 5. Molecular docking simulations revealed that peptides from the most active fractions, including EGIEELLTGTIR, SSPSKHQPPPIR, and LLPRKAK, interact with key residues in the active site of α-amylase. The docking results demonstrated favorable binding energies and stable interactions with critical binding pockets, indicating the peptides strong potential as α-amylase inhibitors. Furthermore, the docking analysis revealed that these peptides interact with both the active site and other regions outside the active site, indicating an uncompetitive inhibition mechanism.